PRINCIPLES OF SAFETY MANAGEMENT OF AIR TRAFFIC FLOWS AND CAPACITY UNDER UNCERTAINTY CONDITIONS - Bo, Wang; Kharchenko, Volodymyr; Chynchenko, Yuriy (Proceedings of National Aviation University (archive), 2016)
Purpose: The aim of this study is to investigate the general principles of safety and capacity management in Aeronautical systems regarding air traffic flows operations under uncertainty conditions. In this work the theoretical framework assessing at the same time both the uncertainty model and flight plans model are proposed. Methods: To study features of safety of air traffic flows and capacity under uncertainty conditions were built the original probabilistic models including Bayesian Network for flight plan and air traffic control sector model based on Poisson Binomial Distribution. Results: We obtained models for safety management of air traffic flows and capacity under uncertainty conditions. We discussed appropriate approach for estimating the parameters of safety of air traffic flows and capacity under uncertainty and Markovian uncertainty model for the flight plan. Discussion: We developed the Bayesian Network for flight plan and air traffic control sector models for safety management of air traffic flows and capacity under uncertainty conditions.